The Role of Science Artificial Intelligence for Trend of Digital HRM - Yunita Niqrisah Dwi Pratiwi (Jurnal Penelitian Pendidikan IPA, 2024)
The science in the world is moving very fast, and technological support is an important factor in the development of this increasingly fast-paced business world. There is something very promising when technology becomes a very reliable tool, as a substitute for the use of muscle-based or human labors. One of the technologies that greatly support the performance of business organizations is the use of digital technology in human resource governance. of these digital technologies, it is still focused on the use of artificial intelligence technology for integrative HR management. This research is a literature review of several articles related to machine learning. The review was conducted from some of the recent research efforts that utilize machine learning. Furthermore, this review is derived from multiple literacies and includes an attempt at problem solving efforts that are divided into section areas from the perspective of each AI category. AI can change the way the human resource management domain functions in an organization. It is making changes in all aspects of human resource management starting from human resource planning. Enormous data is available in human resource information systems (HRIS) available in organizations.